(untitled) (Research, Society and Development, 2021)
Objectives: To analyze the relationship between the Dietary Inflammatory Index (DII), sarcopenia, and frailty syndrome in older people. Methods: A cross-sectional, non-probabilistic study was carried out with 135 older people, attended by a general outpatient clinic. The older people were classified in relation to sarcopenia according to the European Working Group on Sarcopenia in Older People. The frailty classification was made through self-referred questions. The calculation of the DII was made using the iOS application IF RATING®. Association analysis was performed using multiple logistic regression. Results: Of the 135 older people evaluated, 17.78% were classified as sarcopenic and 47.41% as frail. No association was observed between the most inflammatory DII and sarcopenia. Regarding frailty syndrome, older people with a more inflammatory DII were more likely to be frail (OR=3.64; 95%CI=1.24-10.70). Discussion: These results could stimulate actions to promote an anti-inflammatory diet, with a view to preventing frailty in older people.